Implementasi Algoritma Bubble pada Data Akses Pintu Ruangan dengan RFID Berbasis Clien Server - Muhammad Hari Ramadhan (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
At schools provide various room facilities for students to conduct their learning activities. Since each room is utilized according to a specific schedule, a large number of students particularly those using the computer laboratory will make use of these facilities. XYZ Helvetia Private Vocational High School (SMK) provides a computer laboratory for it's students however, students do not enter the lab simultaneously. This scenario inspired the author to sort the students entering the computer laboratory using the Bubble Sort algorithm. The collected data will be processed using this algorithm to arrange the entries chronologically, from earliest to latest. Specifically, the algorithm is designed to sort the entry times of activities recorded via RFID cards a widely used identification technology found at the gates of luxury residential complexes and star-rated hotels. These RFID cards will be linked to the identities of the students entering the school's computer laboratory, and the resulting access data will be stored in an SQL Server database.